PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION DALAM MENINGKATKAN HIGHER ORDER THINKING SKILL DAN KEMAMPUAN KOLABORASI PADA SISWA SEKOLAH DASAR - Muslimin; Kiki Fatkhiyani; Ririn Andriani Kumala Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low learning mastery in mathematics among fifth-grade students at UPTD SDN 3 Kedokan Bunder Wetan. A total of 73.53% or 25 students had not achieved mastery, while only 26.47% or 9 students met the criteria. This issue stemmed from teacher-centered learning and the continued use of conventional methods such as lectures and practice questions. As a solution, the Problem Based Instruction (PBI) model was implemented to place students at the center of the learning process and encourage collaboration in solving real-life problems. The objectives of this study were to examine the implementation of PBI, the improvement in students' Higher Order Thinking Skills (HOTS), and their collaboration skills in learning about three-dimensional shapes. This research employed a Classroom Action Research (CAR) method conducted in two cycles, which included planning, implementation, observation, and reflection stages. The instruments used were observation sheets and written tests. The results showed an increase in HOTS from cycle I, where 22 students achieved mastery (mean score: 66.47; percentage: 64.71%), to cycle II with 29 students achieving mastery (mean score: 76.76; percentage: 85.29%). In addition, students’ collaboration skills also improved, as evidenced by observational data. This research demonstrates that the Problem Based Instruction model is effective in enhancing elementary students’ higher-order thinking and collaboration skills in mathematics learning.